2018
DOI: 10.1007/s40808-018-0552-8
|View full text |Cite|
|
Sign up to set email alerts
|

Artificial recharge of a shallow hard rock aquifer as a climate change mitigation method: model solution from the Czech Republic

Abstract: Drought has always been one of the crucial water management issues especially in a dry climate areas. Recently this matter is emerging also in the Czech Republic and in other parts of the temperate and continental climate zone. With progressing climate changes, we can expect that the current water management systems will often have to adapt to new conditions. This paper offers an evaluation of artificial recharge as a drought mitigation method in areas with crystalline bedrock. The core of the study is a pilot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Prior studies found that even if the change in water policies helped to reach an equilibrium in water balance after years of over-exploitation, the deteriorating groundwater quality may still continue [51]. Artificial recharge for non-confined aquifers has shown to be of great importance when dealing with the improvement of recharge capability of potential areas the sustainment of the aquifer and the capability to cope with stresses on groundwater resources [52,53]. According to the result, the infiltration of 3 × 10 6 m 3 of annual artificial recharge produced a counter effect of on the phreatic level decrement of 2.2 m in the middle zones of the aquifer and 0.9 m of less decrease in the lower parts of the aquifers.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies found that even if the change in water policies helped to reach an equilibrium in water balance after years of over-exploitation, the deteriorating groundwater quality may still continue [51]. Artificial recharge for non-confined aquifers has shown to be of great importance when dealing with the improvement of recharge capability of potential areas the sustainment of the aquifer and the capability to cope with stresses on groundwater resources [52,53]. According to the result, the infiltration of 3 × 10 6 m 3 of annual artificial recharge produced a counter effect of on the phreatic level decrement of 2.2 m in the middle zones of the aquifer and 0.9 m of less decrease in the lower parts of the aquifers.…”
Section: Discussionmentioning
confidence: 99%